Anterior Lumbar Interbody Fusion With and Without an "Access Surgeon": A Systematic Review and Meta-analysis. Issue 10 (15th May 2017) - Phan, Kevin; Xu, Joshua; Scherman, Daniel B.; Rao, Prashanth J.; Mobbs, Ralph J.
Abstract : Study Design: A systematic review and meta-analysis. Objective: The aim of this study was to investigate the outcomes of anterior lumber interbody fusion (ALIF) with and without an "access surgeon." Summary of Background Data: Anterior approaches for spine operations have become increasingly popular but may often involve unfamiliar anatomy and territory for spine surgeons, potentially placing the patient at risk to a greater proportion of approach-related complications. Thus, many spine surgeons require or prefer the assistance of an "access surgeon" to perform the exposure. However, there has been much debate about the necessity of an "access surgeon." Methods: A systematic search of six databases from inception to April 2016 was performed by two independent reviewers. Meta-analysis was used to pool overall rates, and compare the outcomes of ALIF with an access surgeon and without. Results: A total of 58 (8028 patients) studies were included in this meta-analysis. The overall intraoperative complications were similar with and without an "access surgeon." The overall pooled rate of arterial injuries [no access 0.44% vs . access 1.16%, odds ratio (OR) 2.67, P < 0.001], retrograde ejaculation (0.41% vs . 0.96%, OR 2.34, P = 0.005), and ileus (1.93% vs . 2.26%, OR 2.45, P < 0.001) was higher with an "access surgeon." However, the overall pooled rates of peritoneal injury (0.44% vs . 0.16%, OR 0.36, P = 0.034) and neurological injury (0.99% vs . 0.11%, OR 0.11, P < 0.001) were lower with an "access surgeon." Total postoperative complications (5.95% vs . 4.08%, OR 0.67, P < 0.001) were lower with an "access surgeon" along with prosthesis complications (1.59% vs . 0.89%, OR 0.56, P < 0.001) and reoperation rates (2.28% vs . 1.31%, OR 0.57, P < 0.001). Conclusion: Compared with no access surgeon, the use of an access surgeon was associated with similar intraoperative complication rates, higher arterial injuries, retrograde ejaculation, ileus, and lower prosthesis complications, reoperation rates, and postoperative complications. In cases wherein exposure may be difficult, support from an "access surgeon" should be available. Level of Evidence: 1